Dynamic channel assignment algorithms in mobile cellular systems - Weng, Wei. (2009)
This thesis is primarily concerned with dynamic channel assignment (DCA) algorithms in mobile cellular communication systems. Through a study on the analytical model of Maximum Packing (MP), the blocking performance bounds for the traffic-adaptive class of DCA algorithms are derived. The main contribution of this thesis is a new distributed DCA scheme (DDCA), which attempts to optimize the co-channel reuse patterns and to combine the advantages of aggressive and timid DCA schemes. The new DDCA is compared with the lower bounds derived from MP model and other schemes. DDCA algorithm and MP model are further extended to incorporate the handoff issue, which is an important factor in cellular systems. Both the prioritized and the non-prioritized handoff procedures are investigated, respectively. Computer simulation and theoretical calculation show that the blocking performance of the proposed DDCA is slightly inferior to the optimum bounds of MP, but much better than fixed channel assignment (FCA) and hybrid channel assignment (HCA) schemes. However, this slight degradation in performance is a trade-off for less complexity in practical implementation.